Bone marrow and splenic metabolic activity by 18F-FDG PET/CT are associated with noncalcified coronary burden and lipid-rich necrotic core in psoriasis. (14th October 2021) - Patel, N H; Osborne, M; Teague, H; Parel, P; Svirydava, M; Sorokin, A V; Teklu, M; Mayank, G; Zhou, W; Kapoor, P; Rodante, J; Keel, A; et al.
Abstract: Background/Introduction: Psoriasis is an immune-mediated inflammatory skin condition with an increased risk of myocardial infarction (MI). Elevated bone marrow (BM) and splenic hematopoiesis occurs after MI. In stable patients without chronic inflammation, higher splenic hematopoiesis predicts major adverse cardiovascular events (MACE). Nevertheless, studies in humans investigating these relationships in states of chronic inflammation on coronary artery disease features associated with MACE are limited. Purpose: To investigate the relationships between bone marrow and splenic metabolic activity by [18]-fluorodeoxyglucose (FDG) PET/CT and subclinical cardiovascular disease in psoriasis. Methods: Healthy participants (N=30) and psoriasis participants (N=210) were age and sex matched. All participants underwent 18FDG PET/CT and CT angiography (Toshiba 320 slice). Coronary artery plaque characteristics were assessed using QAngio CT (Medis, The Netherlands) and lipid rich necrotic core (LRNC) was assessed using vascuCAP (Elucid Bioimaging, Boston, MA). For tissue metabolic activities target-to-background ratio (TBR) was calculated as the ratio of arterial and venous standardized uptake values (SUV). Results: The psoriasis cohort was middle aged 49.2 (±SD 11.9) years and predominantly male (64%). Those with psoriasis vs. healthy participants had higher BM (1.58 (IQR 1.35–1.89) vs. 1.23 (IQR 1.14–1.35); p<0.001) and splenic (1.40 (IQR 1.21–1.66) vs.1.17 (IQR 1.11–1.26); p<0.001) metabolic activity. After adjustment for cardiovascular risk factors bone marrow metabolic activity was associated with total burden, non-calcified burden (NCB) and LRNC (β=0.36, β=0.39, β=0.26; all p<0.001) respectively. Similar findings were observed for splenic activity (β=0.33, β=0.36, β=0.36; all p<0.001). In ROC analysis, when comparing area under the curve, BM activity better incrementally predicted non-calcified burden and lipid rich necrotic core compared to splenic activity (Figure). Conclusions: BM and splenic metabolic activity are increased in psoriasis. Both are associated with coronary artery disease but there was a slightly stronger association with BM activity compared to splenic activity, These findings warrant further study to understand immune mechanisms underlying these observations. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Heart, Lung and Blood Institute Intramural Research Program in Bethesda, Maryland